The hemophiliac's motorcycle : poems - Andrews, Tom, 1961-2001. (Iowa City : University of Iowa Press, 1994)
In this second wise and passionate book, Tom Andrews explores illness as a major theme, avoiding sentimentality without being merely confessional. He advances his considerable talent with great strength and forcefulness. The poems ae buoyant with humor and mindful of larger mysteries even as they investigate very personal issues. There is an urgency that is compelling; the work is immersed in the private grief of the speaker without excluding the reader.
The hemophiliac's motorcycle -- At Burt Lake -- Ars poetica -- Praying with George Herbert in late winter -- A visit to the cathedral -- Reading Frank O'Hara in the hospital -- Reading the Tao te ching in the hospital -- When comfort arrives -- Evening song -- Hymning the Kanawha -- Codeine diary.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
"Winner of the Iowa poetry prize"
eBooks on EBSCOhost
Keywords: Sick -- Poetry; American poetry -- 20th century; American poetry; Poésie américaine -- 20e siècle.; Poésie américaine.; POETRY -- American -- General; American poetry; Sick; 1900-1999; American poetry; Poetry